Chebyshev type inequalities by using generalized proportional Hadamard fractional integrals via Polya–Szegö inequality with applications. (May 2021) - Set, Erhan; Kashuri, Artion; Mumcu, İlker
Abstract: In this paper, authors give some new Chebyshev type inequalities by using generalized proportional Hadamard fractional integrals via Polya–Szegö inequality. Some interesting applications from main results are established as well.